2012
DOI: 10.1177/1098612x12446906
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of canned therapeutic diets for the management of cats with naturally occurring chronic diarrhea

Abstract: Dietary therapy plays an important role in the management of most gastrointestinal disorders. This study was designed to test the efficacy of a new therapeutic diet for cats with diarrhea, compared to the top selling brand. Sixteen adult cats with chronic diarrhea were grouped and assigned to diet X (Hill's Prescription Diet i/d Feline) or diet Y (Purina Veterinary Diets EN Gastroenteric Feline Formula). Following baseline evaluations, cats were fed their assigned test diet for 4 weeks. Fecal scores (FS; 7=ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…While protein level was similar between the two formulas, the fat and carbohydrate contents varied more widely. Reduced dietary fat has been recommended in patients with gastroenteropathy due to potentially impaired fat absorption (7,8); however, dietary fat was shown to have no difference in clinical response in cats with chronic diarrhea (6). The presence of concurrent chronic pancreatitis has also been an indication for feeding reduced or moderate fat diets in cats with gastroenteropathies (17); however, cats with increased fPL levels were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While protein level was similar between the two formulas, the fat and carbohydrate contents varied more widely. Reduced dietary fat has been recommended in patients with gastroenteropathy due to potentially impaired fat absorption (7,8); however, dietary fat was shown to have no difference in clinical response in cats with chronic diarrhea (6). The presence of concurrent chronic pancreatitis has also been an indication for feeding reduced or moderate fat diets in cats with gastroenteropathies (17); however, cats with increased fPL levels were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
“…Laflamme et al demonstrated improvement in fecal score in 78.2% of 55 cats with chronic diarrhea fed either a low-fat (23% ME) or high-fat (45.1% ME) dry diet containing common ingredients (6). Additionally, two canned therapeutic gastrointestinal formulas containing common ingredients were evaluated for the management of naturally occurring chronic diarrhea, demonstrating resolution to a normal fecal score in up to 46.7% of 15 cats (7).…”
mentioning
confidence: 99%
“…BCS was assessed using a 9‐point scale and assigned as follows: 1, emaciated; 2, very thin; 3, thin; 4, underweight; 5, ideal; 6, overweight; 7, heavy; 8, obese; and 9, grossly obese. Fecal consistency was scored according to a fecal scoring system to provide an objective evaluation to allow comparison between dogs that had CC and EC. Fecal score ranged from 1–7, with 1 being assigned to “very hard and dry,” 2 being assigned to “firm, but not hard,” 3 being assigned to “log‐like,” 4 being assigned to “very moist (soggy) with distinct longitudinal shape,” 5 being assigned to “very moist, but with distinct shape presented in piles,” 6 being assigned to “feces with no defined shape,” and 7 being assigned to “watery.” Because various people were recording observations on feces, fecal scoring charts incorporating 7 photographs and written descriptions corresponding to each of the consistencies were posted in the ICU.…”
Section: Methodsmentioning
confidence: 99%
“…89,123,143 In many, if not most, cats with mild IBD, especially those with a mild to moderate infiltrate of inflammatory cells and without significant weight loss, the initial approach should be to feed a highly digestible diet (this could include novel or hydrolyzed diets) with single-source meat protein, low amounts of highly digestible carbohydrates, and fewer additives, flavorings, or other substances that may be associated with poor digestibility or food intolerance. 89,123,143 In many, if not most, cats with mild IBD, especially those with a mild to moderate infiltrate of inflammatory cells and without significant weight loss, the initial approach should be to feed a highly digestible diet (this could include novel or hydrolyzed diets) with single-source meat protein, low amounts of highly digestible carbohydrates, and fewer additives, flavorings, or other substances that may be associated with poor digestibility or food intolerance.…”
Section: Normalizing the Microbiome: Antibiotics And Probioticsmentioning
confidence: 99%